Multiagent modeling of emotions influence on physiological systems: new concept = Modelowanie wieloagentowe wpływu emocji na układy fizjologiczne: nowa koncepcja - Oleksandr Sokolov; Sebastian Meszyński; Piotr Weber; Dariusz Mikolajewski; Joanna Dreszer; Bibianna Bałaj; Sławomir Grzelak; Włodzisław Duch; Tomasz Komendziński (Kazimierz Wielki University, 2015)
Sokolov Oleksandr, Meszyński Sebastian, Weber Piotr, Mikołajewski Dariusz, Dreszer Joanna, Bałaj Bibianna, Grzelak Sławomir, Duch Włodzisław,  Komendziński Tomasz. Multiagent modeling of emotions influence on physiological systems: new concept = Modelowanie wieloagentowe wpływu emocji na układy fizjologiczne: nowa koncepcja. Journal of Education, Health and Sport. 2015;5(1):221-240. ISSN 2391-8306. DOI:10.5281/zenodo.16252 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A221-240 https://pbn.nauka.gov.pl/works/548059 http://dx.doi.org/10.5281/zenodo.16252 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015.     Multiagent modeling of emotions influence on physiological systems: new concept   Modelowanie wieloagentowe wpływu emocji na układy fizjologiczne: nowa koncepcja   Oleksandr Sokolov1, Sebastian Meszyński1, Piotr Weber2,3, Dariusz Mikołajewski4,1,3, Joanna Dreszer5, 3, Bibianna Bałaj5, 3, Sławomir Grzelak6, Włodzisław Duch1, 3, Tomasz Komendziński5, 3   1 Department of Informatics, Nicolaus Copernicus University, Grudziądzka 5, Toruń, Poland 2 Collegium Medicum, Nicolaus Copernicus University, Bydgoszcz, Poland 3 Neurocognitive Laboratory, Centre for Modern Interdisciplinary Technologies, Nicolaus Copernicus University, Toruń, Poland 4 Institute of Mechanics and Applied Computer Science, Kazimierz Wielki University, Bydgoszcz, Poland 5 Faculty of Humanities, Nicolaus Copernicus University, Toruń, Poland 6 Faculty of Physics, Nicolaus Copernicus University, Toruń, Poland   Address for correspondence: Prof. dr hab. Oleksandr Sokolov Department of Informatics Nicolaus Copernicus University Grudziądzka 5 86-100 Toruń Poland e-mail: osokolov@is.umk.pl   Abstract   Background: Human physiological system belongs to the most complex systems which elements has been described in detail using different mathematical models. Due to  high complexity of elements, the design of whole physiological system depends on the goal of investigations. We would like to concentrate our efforts on emotions influence to physiological systems. That allows to create the model with specific properties that are important to such investigations. Objectives: Primary aim of the study was to assess correlations - statistical relationships between emotional states and physiological parameters.  Secondary aim of this  work was an attempt to describe the physiological processes of subsystems - cardiac, respiratory, glucose-insulin system and their integration into a single information environment for the purpose of analysis, modeling, prediction and real-time control for a variety of diagnostic and analysis of  emotional states. Material and methods: The investigated group consisted of 30 healthy people aged 21 years. In this study multilevel multiagent system is involved in investigation of emotion states modeling. Results: The findings show how relatively simple breathing sensor can be useful both in recording of breath in patients with disorders of consciousness, and also to record the breath in anticipation of certain stimuli in psychological experiments. Conclusions: Proposed concept can constitute another breakthrough in reliable modeling of human physiologic processes. It introduces multi-agent approach into computational analysis of cardiovascular, respiratory, glucose-insulin system, and provides their integration into a single information environment with coherent information flow and behavior.   Key words: cardiocascular system, respiratory system, insulin, emotions, computer simulation.   Streszczenie   Wprowadzenie: Układ fizjologiczny człowieka należy do najbardziej złożonych systemów, a jego poszczególne elementy zostały szczegółowo opisane za pomocą modeli matematycznych. Z powodu ich dużej złożoności projektowanie większych systemów jest uzależnione od celu badania. Nasze wysiłki chcemy skoncentrować na wpływie emocji na systemy fizjologiczne. Cel: Celem podstawowym badania była ocena korelacji - powiązań statystycznych - między stanami emocjonalnymi a parametrami fizjologicznymi. Celem wtórnym badania była próba opisu procesów fizjologicznych za pomocą podsystemów: krążenia, oddechowego i wydzielania insuliny, jak również ich integracji w jedno środowisko informacyjne przydatne do analizy, modelowania, predykcji oraz kontroli w czasie rzeczywistym stanów emocjonalnych w celach diagnostycznych i naukowo-badawczych. Materiał i metody: Badaną grupę stanowiło 30 zdrowych osób w wieku 21 lat. W badaniu wielopoziomowy system wieloagentowy wykorzystano do śledzenia stanów emocjonalnych człowieka. Wyniki: Wyniki badania pokazują, jak stosunkowo prosty czujnik oddechu może być użyteczny zarówno do rejestrowania oddechu u pacjentów z zaburzeniami świadomości, jak również rejestracji oddechu w celu predykcji konkretnego bodźca w eksperymentach psychologicznych. Wnioski: Proponowana koncepcja może stanowić kolejny postęp w wiarygodnym modelowaniu procesów fizjologicznych człowieka. Wprowadza ona modelowanie wieloagentowe do obliczeniowej analizy układów: sercowo-naczyniowego, oddechowego oraz 'glukoza-insulina' oraz zapewnia ich integrację w jednolite środowisko informacyjne ze spójnym przepływam informacji oraz zachowaniem.   Słowa kluczowe: układ sercowo-naczyniowy, układ oddechowy, insulina, emocje, symulacja komputerowa.